2018
DOI: 10.1111/echo.14200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular systolic function in children with repaired tetralogy of Fallot by multiple‐view from single acoustic window with speckle tracking echocardiography

Abstract: Background: Challenges remain in quantitative evaluation of right ventricular (RV) function by echocardiography. Multiple-view assessment is believed to provide a more comprehensive quantification of RV function than conventional single-view analysis. Peak systolic longitudinal RV strain (RVLS) measured by speckle tracking echocardiography (STE) has clinical and prognostic value. No study has investigated RV systolic function in the repaired tetralogy of Fallot (rTOF) using a standardized four-view iRotate mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The measurements used in their study were similar to our approach and demonstrated the following sensitivity and specificity for predicting RV dysfunction: 1) RV fractional area change, 65.9%, 66.7%; and 2) tricuspid annular plane systolic excursion, 70.5%, 78.9% 11 . In 2019, Bao and colleagues evaluated the RV function in 37 children who had undergone surgical repair for TOF, with a mean age of 8 years 6 months 12 . They compared the ejection fraction using cardiac magnetic resonance imaging with ultrasound‐measured RV fractional area change, RV annular plane systolic excursion, and speckle‐tracking analysis of the RV free wall, and found significant correlations between magnetic resonance‐measured ejection fraction and ultrasound‐measured fractional area change and free wall speckle‐tracking strain analysis 12 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The measurements used in their study were similar to our approach and demonstrated the following sensitivity and specificity for predicting RV dysfunction: 1) RV fractional area change, 65.9%, 66.7%; and 2) tricuspid annular plane systolic excursion, 70.5%, 78.9% 11 . In 2019, Bao and colleagues evaluated the RV function in 37 children who had undergone surgical repair for TOF, with a mean age of 8 years 6 months 12 . They compared the ejection fraction using cardiac magnetic resonance imaging with ultrasound‐measured RV fractional area change, RV annular plane systolic excursion, and speckle‐tracking analysis of the RV free wall, and found significant correlations between magnetic resonance‐measured ejection fraction and ultrasound‐measured fractional area change and free wall speckle‐tracking strain analysis 12 …”
Section: Discussionmentioning
confidence: 92%
“…11 In 2019, Bao and colleagues evaluated the RV function in 37 children who had undergone surgical repair for TOF, with a mean age of 8 years 6 months. 12 They compared the ejection fraction using cardiac magnetic resonance imaging with ultrasound-measured RV fractional area change, RV annular plane systolic excursion, and speckle-tracking analysis of the RV free wall, and found significant correlations between magnetic resonance-measured ejection fraction and ultrasoundmeasured fractional area change and free wall speckle-tracking strain analysis. 12 Evaluation of ventricular function in fetuses with TOF has been limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this RV wall is most proximal to the RVOT, the presence of a trans-annular patch from primary surgical reconstruction may explain reduced function in this region. This same multi-plane model has been applied in a cohort of children with repaired ToF [ 21 ], where conversely the lowest longitudinal strain values were reported in the two RV inferior walls. The inferior wall also correlated strongest with cardiac magnetic resonance (CMR) derived RVEF.…”
Section: Discussionmentioning
confidence: 99%
“…All MRI examinations were performed on a 1.5-T Intera Achieva scanner (Philips Medical Systems, Best, The Netherlands). 9 The MRI protocol included retrospectively-gated balanced steady-state free preces- One investigator performed the TomTec calculations twice over several weeks, blinded to the results of the first measurements. The two independent investigators who performed the TomTec measurements on separate days had no knowledge of the results obtained by the other observer.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%